Inoculation of plant growth-promoting bacteria and silicon to optimize nitrogen fertilization in Emerald grass - Vitória Almeida Moreira Girardi; Carlos Eduardo da Silva Oliveira; Bruno Horschut de Lima; Isabela Martins Bueno Gato Gato; Patrick Luan Ferreira dos Santos; Nelson Câmara de Souza Júnior; Arshad Jalal; Marcelo Carvalho Minhoto Teixeira Filho (Ornamental Horticulture)
In Brazil, the main species of turfgrass produced and sold is Emerald grass (Zoysia japonica Steud). However, for high quality production an intensive program of nitrogen fertilization and irrigation is necessary, representing around 21.5% of the costs. Nitrogen is crucial for plant nutrition and growth, increasing photosynthesis and promoting an intense green color. A sustainable alternative is the use of plant growth-promoting bacteria (PGPB), such as Pseudomonas fluorescens and Azospirillum brasilense, which reduce costs and increase profitability by promoting plant growth. Silicon (Si) fertilization also improves plant resistance to biotic and abiotic stresses. The objective of this study was to evaluate the performance of Emerald grass under the effect of inoculation with BPCPs combined with the supply of Si and doses of N, aiming to reduce nitrogen fertilization by 25%. The experiment evaluated soil cover, dark green color index, vegetation index by normalized difference and mass of Emerald grass sod, with 12 treatments combining different doses of N, application of Si and inoculation with BPCPs. The results indicated that the recommended dose of N promoted a higher rate of soil coverage, as well as providing a more intense green in Z. japonica, however, 75% of the recommended dose of N caused greater mass of the mats. However, there was no significant effect of inoculation with BPCPs, nor of Si supply on the analyzed variables.